THE ROLE OF GUY'S STONE SCORE IN MINI-PERCUTANEOUS NEPHROLITHOTOMY (Vietnam Journal of Community Medicine, 2026)
Background: Mini-percutaneous nephrolithotomy (Mini-PCNL) has emerged as a cornerstone in the minimally invasive management of renal calculi. This research aims to validate the clinical utility of the Guy’s Stone Score (GSS) as a preoperative tool for predicting surgical outcomes and potential complications in patients undergoing Mini-PCNL. Methods: A descriptive cross-sectional analysis was performed on 416 patients with renal stones who were treated via single-tract Mini-PCNL under C-arm fluoroscopic guidance at Binh Dan Hospital from January to June 2025. Stone complexity was stratified from GSS I to GSS IV based on preoperative computed tomography (CT) findings. Results: The overall stone-free rate was 83,9%. A significant downward trend in SFR was observed as the GSS increased: 93,3% for GSS I, 89,7% for GSS II, 79,0% for GSS III, and 69,8% for GSS IV (p < 0,001). The overall complication rate was 15,4%,  Guy’s stone score was not significantly associated with complication rates. Conclusions: The Guy’s Stone Score is a simple and effective tool for predicting stone-free rates in Mini-PCNL.
Keywords: Renal calculi, Mini-PCNL, Guy’s Stone Score, Stone-free rate.